A comparative study on online marketing between Airasia and Malaysian Airline System (MAS): the perspective of UNIMAS’s staff / Noridah Adenan - Adenan, Noridah (2007)
The aim of this study is to identify the perspectives of UNIMAS's staffs on the criteria for purchasing airline tickets with respect to AirAsia and Malaysian Airline System (MAS). The study is also to determine the quality of the website provided by AirAsia and MAS and their impact towards customer satisfaction.